A Practical Guide for Advanced Writers in English as a Second Language - Munsell, Paul and Clough, Martha (New York Macmillan Publishing Company, 1984)
A Practical Guide for Advanced Writers is designed for students who are learning English as a second language at the university or graduate level, who are in an upper-intermediate or advanced pre-academic English course (above 65 on the Michigan or above 470 on TOEFL), or who can write as good a composition as the sample labeled 65 in Appendix II.
Keywords: Writing